The Concept of Adverse Drug Reaction Reporting: Awareness among Pharmacy Students in a Nigerian University (2007)
Adverse drug reaction (ADR) is poorly reported globally but more in developing countries with poor participation by health professionals. Currently, there is no known literature on the Nigerian pharmacy students’ knowledge on ADR reporting. Hence the purpose of this study was to find out the level of knowledge of pharmacy students on the concept of pharmacovigilance and adverse drug reaction reporting and also to evaluate their opinions on the National Pharmacovigilance Centre guidelines on adverse drug reaction reporting. A pretested 34-item semi-structured questionnaire was administered among 69 pharmacy undergraduate students in their penultimate and final years that consented to take part in the study, in one of the universities in Nigeria. The study was carried out strictly adhering to the principles outlined in the Helsinki declaration of 1964, which was revised in 1975. The questionnaire used had four sections which included a section on biographical data, a section which evaluated the students’ knowledge on the concept of pharmacovigilance and adverse drug reaction reporting, a section on students personal experiences of adverse drug reactions and modes of reporting them and the final section of the questionnaire evaluated the students’ opinions on the National Pharmacovigilance Centre guidelines for reporting adverse drug reactions. Descriptive statistics, Mann-Whitney U and Kruskal Wallis statistical tests were used to analyze the data obtained. None of the participants knew the sequence of reporting ADR. More than half, 40(58.0%) had heard about pharmacovigilance at symposiums, 7(10.1%) during clinical clerkship program and 18(26.1%) from media jingles. Twenty nine (42.0%) agreed that pharmacovigilance was in their curriculum, however only 16(23.2%) could define the term correctly. None of the participants had seen or used an ADR form prior to the study, but the students could easily identify and describe the type of ADR they had personally experienced in detail, however, they did not know the channel of reporting it. Only 3% reported incidences of personal experience of ADR to the physician while another 3% reported cases of such to the pharmacist. There was a significant difference comparing students’ year of study in the pharmacy program with their opinion scores on the National Pharmacovigilance Centre (NPC) guidelines on ADR reporting (p <0.05). The lack of pharmacovigilance and adverse drug reaction reporting courses in the pharmacy school curriculum result in the poor knowledge of the students on the concept of adverse drug reaction reporting, nonetheless the view and knowledge they had garnered from different sources helped the students in identifying and describing ADR but this is not enough in properly documenting cases of ADRs. Thus, the poor knowledge on ADR reporting among the students requires speedy implementation of new curriculum incorporating pharmacovigilance to enhance the involvement of pharmacists in ADR reporting in Nigeria.